Magazine Aonde Vamos? Ideological and Institutional Network - Chermont, Lucia (Cadernos de Língua e Literatura Hebraica, 2021)
The article proposes to present the national and international groups and institutions that supported the magazine Aonde Vamos? (1943-1976, RJ) their ideological, political and affinity influences. Retracing this universe, through the history of these ideological, political and institutional groups that operated in Brazil in the years in which the magazine was in operation and that had space in the magazine's pages, renumbered or not, to disseminate their activities and or ideological and political projects. The survey of institutions that appeared in the magazine presents itself as an important record of the Jewish institutions that existed and operated in Brazil, highlighting the history of the Jewish community in the country, the construction of a national and/or international Jewish institutional network and its connections.